2013
DOI: 10.15288/jsad.2013.74.369
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant Use, Religiosity, and the Odds of Developing or Maintaining an Alcohol Use Disorder Over Time

Abstract: ABSTRACT. Objective:Little is known about whether cocaine or methamphetamine use, particularly among stimulant users residing in rural areas, is associated with increased odds of developing or maintaining an alcohol use disorder (AUD) over time. One factor that may help to protect some users against the development of an AUD is religiosity. This study examined how stimulant use and religiosity are associated longitudinally with the odds of an AUD among a rural population-based cohort of stimulant users. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The highest prevalence of drug use in this study was among males, supported by other studies (10)(11)(12)(13)(14) . However, the problem should not be neglected without covering the female, that is, although the higher prevalence reaches men, women show an increase in rates of alcohol and other drug use, a cause of concern for researchers who study the pattern of female consumption of psychoactive substances (10,(12)(13)15) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The highest prevalence of drug use in this study was among males, supported by other studies (10)(11)(12)(13)(14) . However, the problem should not be neglected without covering the female, that is, although the higher prevalence reaches men, women show an increase in rates of alcohol and other drug use, a cause of concern for researchers who study the pattern of female consumption of psychoactive substances (10,(12)(13)15) .…”
Section: Discussionsupporting
confidence: 90%
“…Prayer has proved to be a relevant method or one that is most practiced in the context of rehabilitation. In this sense, attending churches influences the recovery of individuals beneficially (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Religiosity is one type of informal support that may help protect against more severe substance use in adults (Borders & Booth, 2013; Koenig et al, 1994; Staton-Tindall et al, 2013). More frequent church attendance, prayer, and considering oneself to be “born again” are associated with lower odds of a recent (6-month) alcohol use disorder in adults (Koenig et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…More frequent church attendance, prayer, and considering oneself to be “born again” are associated with lower odds of a recent (6-month) alcohol use disorder in adults (Koenig et al, 1994). Among a sample of rural substance users, more frequent church attendance is associated with lower odds of developing an alcohol use disorder over a three-year period (Border & Booth, 2013). Higher scores on a measure of existential well-being are associated with fewer days (in the past 30 days) using alcohol and cocaine among a sample of African American women (Staton-Tindall et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous research has shown the protective influence of religion against the initiation of substance use, the development of substance abuse disorders, the receipt of substance abuse treatment, and other HIV‐related substance use risk behaviors . Several dimensions of religion have also been associated with HIV‐related sexual risk behaviors, including increased HIV testing, fewer sexual partners, and higher self‐efficacy in refusing risky sexual encounters and discussing HIV prevention .…”
mentioning
confidence: 99%